WO WA DANCE : WAR DANCE OF PLOLY VILLAGE ( PELERI ) MAKIAN ISLAND DISTRICT - Hasim, Rustam; Hasim, Daud; Amalia, Rasty (Universitas Hasanuddin, 2025)
The Makian tribe is one of the tribes originating from the North Maluku Islands region, especially those inhabiting Makian Island, which is located southwest of Halmahera Island. This tribe has a unique cultural wealth, including language, customs, and traditional arts such as dance and music. Wo Wa Dance is performed by men and has a dashing, firm, and spirited movement, often equipped with attributes such as spears, shields, swords, or traditional weapons. According to Legend, Wo-Wa Dance is a dance used to conquer the rebellion carried out by Kapita Takome (warlord) in the Sulamadaha region. Kapita Takome and his followers showed their disloyal attitude and declared war on the Ternate Sultanate. To overcome the rebellion, troops were sent from Makian Island led by Kapita Peleri (Ploly).